Digital marketing of commercial breastmilk substitutes and baby foods: strategies, and recommendations for its regulation in Mexico - Pedro Javier Mota-Castillo; Mishel Unar-Munguía; Andrea Santos-Guzmán; Marena Ceballos-Rasgado; Lizbeth Tolentino-Mayo; Simón Barquera; Matthias Sachse Aguilera; Fernanda Cobo Armijo; Anabelle Bonvecchio (BMC, 2023)
Abstract Background Parents are exposed to breastmilk substitutes and baby foods marketing on the internet and social media, which hinders adequate breastfeeding and complementary feeding. This study identifies digital marketing strategies for breastmilk substitutes, specifically commercial milk formula and baby foods used by the industry to influence infant and young children's feeding practices in Mexico and proposes regulatory recommendations that can be useful for similar countries. Methods Qualitative study based on the CLICK monitoring framework developed by the World Health Organization, adapted for digital marketing of commercial milk formula and baby foods. Semi-structured interviews (n = 53) with key actors were conducted between November 2020 and March 2021, and used grounded theory for the analysis and interpretation with the MAXQDA 20 software. Results Commercial milk formula and baby food companies use digital media to contact and persuade parents to use their products by sending electronic newsletters with advertising. Companies hire influencers to market their products because there is no regulation prohibiting the advertisement of breastmilk substitutes on social media, and promote formula among health professionals inviting them to participate in sponsored webinars on infant nutrition, ignoring conflict of interest and the International Code of Marketing of Breastmilk Substitutes. Parents trust formula and baby food advertisements, which use emotional messages and health and nutrition claims to encourage their consumption. Health professionals consider that claims contribute to the indiscriminate use of formula, and some actors propose the use of plain packaging for these products. Conclusions Breastmilk substitutes companies promote their products in digital media using unethical strategies that fail to comply with the International Code of Marketing of Breastmilk Substitutes. They generate strong conflicts of interest with health professionals, taking advantage of legal framework gaps and the lack of monitoring and effective sanctions for non-compliers. Updating the legal framework and monitoring compliance, including digital media, is urgently needed to protect children's right to breastfeeding, healthy nutrition and life, and the rights of women to health and informed decision-making.